The Role of Islamic Values in the Development of Science and Technology: Perspectives from Al-Islam and Muhammadiyah - Rohma, Allifatur; Nurhayati, Neneng; Yuniarti, Yanti; Jamroji, Bagus (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
This study aims to examine the role of Islamic values from the perspe ctive of Al-Islam and Muhammadiyah in guiding the development of science and technology toward human welfare and moral responsibility. Using a qualitative philosophical library research approach, this study analyzes the Qur’an, Hadith, Muhammadiyah documents, and relevant scholarly literature through thematic and hermeneutic analysis. The findings show that Islamic values position science and technology as a trust directed toward maslahah and the realization of hayatan tayyibah.